Analisis Pengaruh Fraud Pentagon Dalam Mendeteksi Tingkat Accounting Irregularities Dengan Komite Audit Sebagai Variabel Moderasi - Salma, Difa Putri; Nurlaili, Nurlaili; Rifan, Dinda Fali (Fakultas Ekonomi Prodi Akuntansi, 2024)
This study aims to determine the effect of the Fraud Pentagon on the occurrence of Accounting Irregularities with the audit committee as a moderating variable in manufacturing companies listed on the Jakarta Islamic Index (JII) in 2018-2023. This study uses quantitative research with secondary data. The population in this study were manufacturing companies listed on the Jakarta Islamic Index (JII) in 2018-2013. Sampling using purposive sampling method. The data analysis method used is the MRA test using the IBM SPSS Version 20 program. The results showed that the Fraud Pentagon proxy variable, Nature Of Industry had a positive and significant effect on the occurrence of Accounting Irregularities. Total Accruals have a positive and significant effect on the occurrence of Accounting Irregularities. Change of Directors has a positive and significant effect on the occurrence of Accounting Irregularities. Financial Stability, Ineffective Monitoring, and CEO Picture proxy variables have no effect on the occurrence of Accounting Irregularities and the Audit Committee cannot moderate, meaning that the existence of an Audit Committee in the company is only a fulfillment of applicable regulations.